Finding Fela [videorecording (DVD)] - Fela, 1938-1997 (2015)
Fela Anikulapo-Kuti created a new musical movement, Afrobeat, a combination of jazz, funk, and Nigerian percussion styles. It was also a political force, a propulsive delivery system of Fela's revolutionary ideas, pitched against the dictatorial Nigerian government of the 1970s and 1980s. His influence helped bring a tilt towards democracy in Nigeria and promoted Pan-Africanist politics to the world. The power and potency of Fela's music and message endure today.